KOMODIFIKASI BERITA PENYELENGGARAN IBADAH HAJI DI SKH REPUBLIKA - Hadi, Syaipul (Alhadharah: Jurnal Ilmu Dakwah, 2015)
This paper reviewed the fact that many news stories about the Hajj that is always repeated every year, without being able to reveal how to parse problems that always accompany the implementation of the pilgrimage. Viewed from the standpoint of political economy, the news on Hajj is an economic commodity that is profitable for media owners. Therefore, the news about the Hajj continues to be exploited in order to improve the rating or newspaper circulation. It was concluded that the commodification of news on Hajj in Republika daily newspaper was part of the commodification of Islam. Commodification is done with a lot of news coverage of the Hajj which contains information about the Hajj. Commodification is also associated with an audience of many Republika?s readers thus attracting advertisers to advertise in the daily.Makalah ini mengulas tentang fakta banyaknya berita-berita tentang haji yang selalu berulang-ulang setiap tahun, tanpa dapat mengungkapkan bagaimana mengurai masalah yang selalu menyertai pelaksanaan ibadah haji. Dilihat dari sudut pandang ekonomi politik, pemberitaan haji merupakan komoditas ekonomi yang menguntungkan bagi pemilik media. Karena itu, berita-berita tentang haji terus dieksploitasi guna meningkatkan rating berita atau oplah surat kabar. Disimpulkan bahwa komodifikasi berita haji di SKH Republika merupakan bagian dari komodifikasi Islam. Komodifikasi dilakukan dengan banyak memuat berita liputan haji yang berisi informasi tentang haji. Komodifikasi juga terkait dengan khalayak pembaca Republika yang jumlahnya banyak sehingga menarik pengiklan untuk beriklan di harian Republika.